PWE-088 Abnormal Liver Function Tests Following use of Thiopurines in a Large Cohort of Inflammatory Bowel Disease Patients-Do TPMT Levels Matter?. (4th June 2013) - Harrison, L; Nelson, A; Cole, R; Bennett, T; Abouda, G; Sebastian, S
Abstract : Introduction: Thiopurine (azathioprine and 6 –Mercaptopurine (6MP)) use is one of the aetiologies for abnormal liver function tests in patients with inflammatory bowel disease. Some studies report hepatotoxicity is associated with high levels of the 6-MP metabolite, 6-methylmercaptopurine ribonucleotide (6-MMPR). This may indicate that hepatotoxicity correlates with the level of thiopurine methyl transferase enzyme (TPMT) activity. The aim of this study was to assess the prevalence of 6-MP/Azathioprine hepatotoxicity in a large cohort of IBD patients and to determine its correlation with serum TPMT levels in adult IBD patients. Methods: Patients with IBD initiated on thiopurines following TPMT assay were included and follow up data collected on development of abnormal liver function tests. We excluded patients who had abnormal LTs before initiation of AZT. We used Council for International Organizations of Medical Sciences (CIOMS) definitions to determine the grade of hepatic alterations : "Abnormality of LTs" defined as an increase in AST, ALT, AP, GGT, or total bilirubin between N (upper limit of the normal range) and 2 N. "Liver injury" (or "hepatotoxicity") defined as an increase of over 2 N in the aforementioned LTs. Data was collected on demographic factors, concomitant medication use and additional factors favouring liver injury. TPMT levels were categorised as low, normal and high based on local laboratory reference standards. Results: 311 IBD patients (249 Crohn's disease, 53 ulcerative colitis and 9 undifferentiated) were included. The median age was 35 years (range, 14–86 years). Abnormal LTs developed in 66 (21.2%) of patients. Hepatotoxicity was noted in 29 (9.3%) of patients with 18 of these patients (6%) needing to stop thiopurines. None of the patients with high TPMT developed abnormal LTs or hepatotoxicity. 27 of the 29 patients with hepatotoxicity had normal TPMT levels and remaining 2 had low TPMT levels. Conclusion: Abnormal liver tests following initiation of thioprines occur in a relatively high proportion of patients, but the development of hepatotoxicity necessitating treatment cessation occurs only in 6% of cases even in the era of concomitant anti-TNF therapy. Pre treatment TPMT levels do not appear to have an impact on the probability of development of hepatotoxicity. Disclosure of Interest: None Declared.